2019
DOI: 10.21837/pm.v17i10.640
|View full text |Cite
|
Sign up to set email alerts
|

Income Perspective on the Factors Influencing Households’ Recycling Intention: Implications From the Extended Theory of Planned Behaviour

Abstract: Although few studies have attempted to explain residents’ waste handling behaviour from social and psychological perspective, yet, there is little understanding regarding the influence of households’ moral obligation, consequences awareness, and perceived lack of facilitating conditions on forming recycling intention. This study aims at investigating the key determinants of household recycling intention using the extended theory of planned behaviour (TPB). Data collected from 422 households in Kano metropolis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The results of the present study also showed that attitude is the strong predictor towards solid waste management practice among the households in Butajira town. This is consistent with studies conducted in Kenya, Nigeria, Malaysia and China [9,22,26,27]. This might be due to those individuals who believed that solid waste management practice could lead a healthier life, prevent death related to poor waste management, prevent the risk of infection, promote the quality of the urban environment were more likely to have a favorable attitude and then more intended to solid waste management practice.…”
Section: Plos Onesupporting
confidence: 89%
“…The results of the present study also showed that attitude is the strong predictor towards solid waste management practice among the households in Butajira town. This is consistent with studies conducted in Kenya, Nigeria, Malaysia and China [9,22,26,27]. This might be due to those individuals who believed that solid waste management practice could lead a healthier life, prevent death related to poor waste management, prevent the risk of infection, promote the quality of the urban environment were more likely to have a favorable attitude and then more intended to solid waste management practice.…”
Section: Plos Onesupporting
confidence: 89%
“…This means that, the higher the awareness of the benefit of waste sorting and recycling, the higher a household's level of willingness toward sustainable waste handling practices. Most of the respondents in this study responded that they were aware of the benefits of sorting waste and recycling it by indicating that recycling saves money and creates jobs [49]. This is reflected in the results of the t-test, which showed a significant difference in the mean score of government facilitators among low-and high-income households.…”
Section: Comparing the Three Different Income Level Groups With Damma...mentioning
confidence: 71%
“…This finding is contrary to Wan et al (2014) [17], who revealed that positive attitudes and intention toward recycling tend to be low when there are no recycling facilities and/or local collections. The overall ANOVA test revealed significant differences among the three income groups, indicating that each income group in Dammam City has a particular 337 factor motivating their willingness to participate in waste sorting and recycling, as suggested by Khalil et al (2019).…”
Section: Comparing the Three Different Income Level Groups With Damma...mentioning
confidence: 82%
See 1 more Smart Citation
“…However, the waste management in these cities offers lessons on effective strategies, technologies, and policies that could be relevant to the planning of KNC's MSW collection system. Additionally, Khalil et al (2019) offer useful recommendations for recycling policies that prioritize the creation of households' intentions. These proposals include the provision of recycling facilities, the encouragement of participation through market-driven recycling programs, and the promotion of recycling awareness and education.…”
Section: Literature Reviewmentioning
confidence: 99%